Ureteric bupivicaine infusion for loin pain haematuria syndrome - Ahmed, P (The Royal College of Surgeons of England, 2010)
INTRODUCTION: Loin pain haematuria syndrome is a common problem with complications including opiate dependence. Morbidity treatments include intra-ureteric capsaicin infusion, nephrectomy, autotransplantation and nephrolysis. We explored the use of flexible cystoscopic infusion of intra-ureteric bupivicaine. PATIENTS AND METHODS: Patients presenting with chronic loin pain underwent urological and nephrological evaluation. Bupivicaine (0.5%, 20 ml) was infused via an intra-ureteric catheter under flexible cystoscopic guidance. Repeat infusions were offered if indicated. RESULTS: Sixteen of 17 patients with 1-year follow-up responded and were satisfied. Twelve of these required repeat infusions (mean, 2.9 infusions). The procedures were well tolerated by all patients without adverse effects. CONCLUSIONS: Intra-ureteric bupivicaine infusion has a place in the management of patients with chronic renal pain. It offers a minimally invasive alternative to other treatments. This procedure warrants further investigation within a randomised, controlled trial setting.